INTRODUCTION INTERDISCIPLINARY NATURE TO HIGHER EDUCATION INSTITUTIONS - Jabbarov, Sardor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: This article well explains the basics of interdisciplinary education and analyzes the importance, benefits and handicaps of interdisciplinary courses in higher education systems. It also shortly discusses the history of interdisciplinary approach and future prospects in a short and long term. Finally, it provides some aspects need to be considered by faculties and students while developing and selecting one of these courses.